High-performance flexible all-solid-state aqueous rechargeable Zn–MnO2 microbatteries integrated with wearable pressure sensors. Issue 30 (23rd July 2018) - He, Bing; Zhang, Qichong; Li, Lianhui; Sun, Juan; Man, Ping; Zhou, Zhenyu; Li, Qiulong; Guo, Jiabin; Xie, Liyan; Li, Chaowei; Wang, Xiaona; Zhao, Jingxin; et al.
Abstract : A self-powering, multifunctional, miniaturized integrated system was designed to achieve real-time health monitoring both statically and dynamically. Abstract : The ever-increasing demand for smart personal electronics has promoted the rapid development of wearable multiple functionalities integrated configurations. However, it is still a great challenge to realize both high-performance energy storage devices and functional sensors in a single device to obtain a stable, self-powering, multifunctional, miniaturized integrated system. Herein, we report an ultrathin microbattery-pressure sensor integrated system to simultaneously achieve energy storage and pressure detection in a single device. Energy storage is achieved by an in-plane, interdigitated, flexible, all-solid-state, aqueous rechargeable Ni@MnO2 //Zn microbattery in a thin polydimethylsiloxane film, using MnO2 nanosheets directly deposited on highly conductive 3D Ni skeletons (Ni@MnO2 ) as an advanced binder-free cathode. Benefiting from synergy between the high electrochemical performance of MnO2 and the outstanding conductivity of 3D highly conductive Ni skeletons, the assembled Ni@MnO2 //Zn microbattery displays a high capacity of 0.718 mA h cm −2 and a correspondingly impressive energy density of 0.98 mW h cm −2 . More importantly, the wearable pressure sensor, which is powered by the integrated Ni@MnO2 //Zn microbattery, can achieve real-time health monitoring both statically and dynamically. Thus, this work paves the way to develop high-performance, multifunctional, miniaturized integrated configurations for portable and wearable electronics.